Gender determination in deciduous pulp tissue using Barr bodies by comparing Feulgen stain, acridine orange, and Papanicolaou stain - Yoithapprabhunath Thuckanaickenpalayam Ragunathan; Aarthi Arumugam; Ganapathy Nalliappan; Dineshshankar Janardhanam; Illayaraja Vadivel; Thangadurai Maheswaran (Wolters Kluwer Medknow Publications, 2022)
Background: Age, sex, stature, and ethnic background are considered a main attributes of biological identity of the individual, which are also called the "Big Four" in forensic. Human identification is of chief importance, in both legal and humanitarian purpose. Teeth can remain virtually unaffected and survive long after other soft tissue and skeletal tissues were destroyed. Hence, its implication in personal identification was gained popularity and high accuracy. Aim and Objective: The aim and objective of the study were to determine the reliability of gender determination from deciduous dental pulp tissue by comparing Feulgen stain, acridine orange, and Papanicolaou stain. Materials and Methods: This study was carried out on 25 samples, out of which 14 female teeth and 11 male teeth. The pulp was collected from the teeth undergoing pulpectomy. Then, the pulp tissue was transferred to the centrifuge tube containing Carnoy's fixative. After centrifugation, the cells were collected and stained using Feulgen stain, acridine orange, and Papanicolaou stain. Results: The reliability of gender determination is significant, with the female shows 100% positive results and the male shows negative. The Papanicolaou stain shows better nuclear morphology while comparing with Feulgen and acridine orange. Conclusion: Hence, gender determination can be identified using deciduous dental pulp.